Pengaruh Kebudayaan K-Pop Terhadap Mode Pakaian Remaja Di Ponorogo - Apsa Pandu Winata; Ady Bagoes Jagat Satria Vandea; Andhita Risko Faristiana (Universitas Katolik Widya Karya Malang, 2023)
K-Pop, has become increasingly popular in Ponorogo in recent years. One significant impact of this popularity is the change in the clothing fashion of teenagers in Ponorogo. This article will discuss the influence of K-Pop culture on teenagers' clothing fashion in Ponorogo. K-Pop has brought a different and unique fashion style, which influences fashion trends in Ponorogo. Ponorogo teenagers are especially impressed by the styles popularized by K-Pop stars, including hairstyles, make-up, and accessories. The fashion industry in Korea has grown rapidly along with the popularity of K-Pop, and this has also had an impact on fashion in Ponorogo. Several Korean fashion brands have entered the Ponorogo market and offer products inspired by K-Pop fashion styles. As a result, the influence of K-Pop culture on teenagers' clothing fashion in Ponorogo is significant. There is a shift in fashion trends from the traditional Ponorogo style to the more modern and unique K-Pop style. However, this can also lead to problems such as an imbalance between indigenous and imported cultures. Overall, the influence of K-Pop culture on teenagers' clothing fashion in Ponorogo has brought many changes and become a popular trend. However, it is important for P communities to maintain their cultural identity and not be overly influenced by outside cultures.